Moderasi Profitabilitas Atas Pengaruh Corporate Social Responsibility terhadap Nilai Perusahaan - Rafika Sari; Renny Aziatul Febrianti (Universitas Indo Global Mandiri)
The purpose of this study is to determine whether profitability can moderate the relationship between corporate social responsibility as well as to see whether there is an influence between corporate social responsibility on corporate value in consumer goods sector companies listed on the IDX during 2017 until carrying out the pandemic period in 2019. Research linking the relationship between these variables and testing it empirically. The results showed a relationship between the social aspects of corporate social responsibility in a company to firm value, either partially or simultaneously. The data analysis method used was linear regression. This method was chosen because the reference shows that there is a match between the analysis tool and the variables studied. The sample in this study uses purposive sampling so that the number of samples is 51 companies taken with the selected criteria. The results of the study indicate that profitability can moderate the relationship between corporate social resonance and there is a positive but insignificant influence between corporate social responsibility and firm value. The results of the study reject the theory and the first hypothesis which suggests that there is a significant influence on firm value, this is because some companies during the pandemic did not carry out corporate social responsibility or did not report it on their annual reports, while the results of this study accept the second hypothesis which states that profitability is able to moderate. the influence of corporate social responsibility on company value, this proves the economic relationship in the social contract which explains that the higher the profit, the greater the company's ability to fulfill its social responsibility and gain the trust of its stakeholders, thereby increasing the company's value.Keywords: Profitability, CSR , Company Value